Big-brained people are smarter: A meta-analysis of the relationship between in vivo brain volume and intelligence - McDaniel, Michael A. (Intelligence, 2005)
The relationship between brain volume and intelligence has been a topic of a scientific debate since at least the 1830s. To address the debate, a meta-analysis of the relationship between in vivo brain volume and intelligence was conducted. Based on 37 samples across 1530 people, the population correlation was estimated at 0.33. The correlation is higher for females than males. It is also higher for adults than children. For all age and sex groups, it is clear that brain volume is positively correlated with intelligence.
Keywords: neurosciences